2017
DOI: 10.1186/s13027-017-0143-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-pulmonary cancer risk following tuberculosis: a nationwide retrospective cohort study in Lithuania

Abstract: BackgroundLithuania remains one of the highest tuberculosis burden countries in Europe. Epidemiological studies have long pointed to infections as important factors of cancer aetiology, but the association between tuberculosis and the risk of non-pulmonary cancers has rarely been tested and results have been inconsistent. The aim of this population-based cohort study was to examine the risk of cancer among patients diagnosed with tuberculosis using data from Lithuanian Tuberculosis, Cancer and Resident’s Regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…Prior TB might increase the risks of lung cancer and some extrapulmonary cancers, including hematologic malignancies, esophageal cancer, genitourinary cancers, head and neck cancer, breast cancer, and “other” cancers. In accord with several prior studies [ 9 , 11 , 13 , 15 , 21 ], our results indicate an association between TB and certain cancer types (Table 3 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Prior TB might increase the risks of lung cancer and some extrapulmonary cancers, including hematologic malignancies, esophageal cancer, genitourinary cancers, head and neck cancer, breast cancer, and “other” cancers. In accord with several prior studies [ 9 , 11 , 13 , 15 , 21 ], our results indicate an association between TB and certain cancer types (Table 3 ).…”
Section: Discussionsupporting
confidence: 93%
“…TB may induce a chronic inflammatory state and impair T-cell-mediated immunity, contributing to the development of cancer [8][9][10]. Indeed, a number of epidemiologic studies have shown that the risk of cancer is the greatest in the first 2 years after the diagnosis of TB [9][10][11][12][13] but remains elevated for long periods [12,[14][15][16][17][18]. Understanding the risk of the development of cancer after TB in a highly endemic area has some practical clinical significance, such as improving the prevention and diagnosis of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In accord with several prior studies [2,6,8,10,14], our results indicate an association between TB and certain cancer types (Table 3). Notably, prior TB has been consistently found to be associated with a subsequent high risk of hematological malignancies, including non-Hodgkin's lymphoma, Hodgkin's lymphoma, multiple myeloma, and leukemia.…”
Section: Discussionsupporting
confidence: 93%
“…[4] In addition, the burden of multidrug-resistant and extensively drug-resistant TB cases was also found to be substantial in the Xinjiang area. [5] A number of epidemiologic studies have shown that the risk of cancer is the greatest in the rst two years after the diagnosis of TB diagnosis [2,3,[6][7][8] but remains elevated for long periods. [7,[9][10][11][12][13] However, limited data are available from western China to support the link between cancer and TB.…”
Section: Introductionmentioning
confidence: 99%
“…Although no coexisting tumors were identified in this study, there have been many reports showing the coexistence of LTB infections and cancers, which suggest that one disease could facilitate the other. [ 29 , 31 , 32 ] Biopsies were often selected at exophytic or ulcerative lesions. We found that exophytic lesions usually consisted of epithelioid granulomas, accompanied by decreased areas of caseous necrosis.…”
Section: Discussionmentioning
confidence: 99%